Sphingosine-1-phosphate: Potential mediator in retinal proliferative disorders? - Simon, Maria Victoria (2024)
Introduction Fibrosis is a common feature of retina proliferative diseases, as diabetic retinopathy and proliferative vitreoretinopathy, which lead to vision loss. Dysregulation of cell attachment, migration and de-differentiation of Müller glial cells (MGC) and retinal pigment epithelium (RPE) cells, which provide structural and metabolic support in the retina contribute to the fibrotic process. Modulation of this process might hold the key to prevent the development of proliferative retinopaties. Sphingolipids such as sphingosine-1- phosphate (S1P), which regulates critical cellular functions, like proliferation, inflammation, migration, survival and differentiation, advance fibrosis in different tissues, but their role in the retina is still unclear. Objectives To study the role of S1P in the regulation of processes leading to fibrosis in the retina. Methods Primary MGC cultures and RPE cell line cultures (ARPE-19 and D407) were exposed to 5 uM S1P for 24 h. We incubated cell cultures with sphingosine kinase inhibitors SphKI2 and PF-543, to study the role of endogenous S1P, with W146, JTE-013 and BML241, specific S1P1, S1P2 and S1P3 antagonists, respectively, to analyze the involvement of S1P receptors . The ERK/MAPK and PI3K signaling pathways were analyzed with specific inhibitors U0126 and Ly294002, respectively. Cell migration was de- termined by the scratch wound assay, RPE cell morphology and localization of adherent proteins were analyzed by immunocyto- chemistry, pro-inflammatory cytokines were evaluated by PCR. Results We demonstrated that MGC synthesize S1P, which signals through S1P3 and the PI3K and ERK/MAPK pathways to induce gli- al migration. S1P also stimulated RPE cell migration and this effect required endogenous synthesis of S1P. S1P increased the transcription of pro-inflammatory cytokines IL-6 and IL-8, and of epithelial to mesenchymal transition (EMT) marker α-smooth muscle actin (α-SMA) in RPE cells. Blocking S1P syntesis led to RPE cell retraction, and to the disassembly of focal adhesions and cell-cell contacts. Exogenous S1P prevented these changes, signalling through S1P1 and S1P2. Conclusion Our results showed that S1P promoted MGC and RPE cell migration, and RPE release of pro-inflammatory cytokines, which might contribute to retinal fibrosis. However, they also imply that endogenous S1P regulates RPE proper attachment to neighboring cells and to the extracellular matrix, thus preserving monolayer integrity. This suggests a dual role for S1P in the retina, either protective or deletereous. Uncovering the molecular cues that modulate these S1P effects might provide new tools for treating retina proliferative disorders.